Stability analysis of oil yield in oil palm (Elaeis guineensis) progenies in different environments - Rafii M.Y.; Jalani B.S.; Rajanaidu N.; Kushairi A.; Puteh A.; Latif M.A. (Fundacao de Pesquisas Cientificas de Ribeirao Preto, 2024)
Indexed by WOS/ Scopus